DEVELOPMENT OF AN INTEGRATED CAMPUS SECURITY ALERTING SYSTEM (Nigerian Journal of Technology, 2016)
Providing safe and secured environment for staff, students and visitors in colleges and university is a major task that must be achieved. With the recent level of attack on campuses by insurgents and other internal social vices, there is the need for urgent protective means of securing lives and property on campus. This work presents an integrated alerting system which uses both the Internet Protocol (IP) cameras and micro-switches for monitoring security situations thereby providing an immediate alerting signal to the security personnel. The system has the input unit, processing unit, control unit and the power supply unit as its building blocks. The design of the alerting system uses PIC16F877A Microcontroller to control and process information sent from the input unit. The processed information is sent to the output unit where it is displayed by a liquid crystal display (LCD) and an audible alarm is equally activated. It was simulated with Proteus 8, and results show improvement in security monitoring. However there is need for structural modification on the campuses for effective implementation of this design. http://dx.doi.org/10.4314/njt.v35i4.26